2020
DOI: 10.1002/cmdc.202000260
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Antiviral Perfluoroalkyl Derivatives of Teicoplanin and Vancomycin

Abstract: The limited scope of antiviral drugs and increasing problem of antiviral drug resistance represent a global health threat. Glycopeptide antibiotics and their lipophilic derivatives have emerged as relevant inhibitors of diverse viruses. Herein, we describe a new strategy for the synthesis of dual hydrophobic and lipophobic derivatives of glycopeptides to produce selective antiviral agents without membrane‐disrupting activity. Perfluorobutyl and perfluorooctyl moieties were attached through linkers of different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 46 publications
2
24
0
Order By: Relevance
“…The authors concluded that the anti-SARS-CoV-2 activity of teicoplanin could be more effective at early infections, which is in accordance with recent results by Zhao et al [20]. We, and others, have demonstrated that the antiviral spectrum and efficacy of g peptide antibiotics can be increased by lipophilic modifications, and a number of isynthetic lipophilic derivatives of the antibiotics vancomycin, teicoplanin and rist have been published that showed good antiviral activity against coronaviruses [25-2 well as HIV [28], flaviviruses [29] and influenza viruses [26,27,[30][31][32][33][34]. Unfortunatel high antiviral activity is often associated with cytotoxicity [33,34].…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…The authors concluded that the anti-SARS-CoV-2 activity of teicoplanin could be more effective at early infections, which is in accordance with recent results by Zhao et al [20]. We, and others, have demonstrated that the antiviral spectrum and efficacy of g peptide antibiotics can be increased by lipophilic modifications, and a number of isynthetic lipophilic derivatives of the antibiotics vancomycin, teicoplanin and rist have been published that showed good antiviral activity against coronaviruses [25-2 well as HIV [28], flaviviruses [29] and influenza viruses [26,27,[30][31][32][33][34]. Unfortunatel high antiviral activity is often associated with cytotoxicity [33,34].…”
Section: Introductionsupporting
confidence: 89%
“…Carotenoids are natural hydrophobic products with 40 carbon atoms, having c gated polyenic structures and possessing a number of beneficial biological activiti cluding antioxidant and immune enhancer properties, the regression of malignant le and mutagenesis inhibition [35][36][37]. Carotenoids are susceptible to oxidation; the We, and others, have demonstrated that the antiviral spectrum and efficacy of glycopeptide antibiotics can be increased by lipophilic modifications, and a number of semisynthetic lipophilic derivatives of the antibiotics vancomycin, teicoplanin and ristocetin have been published that showed good antiviral activity against coronaviruses [25][26][27], as well as HIV [28], flaviviruses [29] and influenza viruses [26,27,[30][31][32][33][34]. Unfortunately, the high antiviral activity is often associated with cytotoxicity [33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Teicoplanin is a glycopeptide antibiotic with its main activity to treat bacterial infection (Reynolds, 1989;Zhou et al, 2016). In vitro experiments demonstrated that this drug inhibited cell entry of the EBOV into primary human umbilical vein endothelial cells, A549 cells, HeLa cells, and THP-1 cells with an IC50 of 0.34 μM (Zhou et al, 2016), as well as its derivatives demonstrated antiviral activity against influenza strains, vaccinia, herpes, and human coronavirus (Bereczki et al, 2020). Recently, it was published that teicoplanin potently blocks the HIV-luc/ 2019-nCoV-S pseudoviruses entry into human A549 cells with a IC50 of 1.66 μM, suggesting this could be caused by the cathepsin L inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the light-promoted radical addition reaction [25] of commercially available perfluoroalkyl iodides onto the C19-C20 double bond allows the introduction of fluorous side chains into the pleuromutilin skeleton. Importantly, perfluoroalkylated derivatives of teicoplanin and vancomycin have recently been synthesized [26] by our group, and the introduced perfluorous side chains having a dual hydrophobic and lipophobic character [27] have remarkably improved the antimicrobial properties of the parent glycopeptide antibiotics.…”
Section: General Methodsmentioning
confidence: 99%